An integrative analysis of ASCL1 in breast cancer and inhibition of ASCL1 increases paclitaxel sensitivity by activating ferroptosis via the CREB1/GPX4 axis - Yang, Xiaolu; Li, Yilun; Peng, Yaqi; Chang, Yuan; He, Binglu; Zhang, Tianqi; Zhang, Shiyu; Geng, Cuizhi; Liu, Yunjiang; Li, Xiaolong; Hao, Jun; Ma, Li (Frontiers in Immunology, 2025)
ObjectiveOur previous study found that Achaete-scute complex homolog 1 (ASCL1) is involved in classifying BC subtypes with different prognostic and pathological characteristics. However, the biological role of ASCL1 in BC still remains largely unexplored. This study aims to elucidate the function of ASCL1 in BC using bioinformatics analyses, as well as in vitro and in vivo experimental approaches.MethodsData from the TCGA, GEO, and Human Protein Atlas databases were utilized to evaluate ASCL1 expression in BC and its association with patient prognosis. Genetic alterations in ASCL1 were assessed through the COSMIC and cBioPortal databases, while the TIMER2.0 database provided insights into the relationship between ASCL1 expression and key gene mutations in BC. The GDSC database was used to examine correlations between ASCL1 levels and sensitivity to standard chemotherapeutic agents. Associations between ASCL1 expression and cytokines, immunomodulatory factors, MHC molecules, and receptors were analyzed using Pearson and Spearman correlation methods. The TIP database was employed to investigate the connection between ASCL1 expression and immunoreactivity scores, and six computational approaches were applied to evaluate immune cell infiltration. Functional assays were conducted on BC cell lines MCF-7 and MDA-MB-231, and nude mouse models were used for in vivo studies.ResultsASCL1 was found to be upregulated in BC and correlated with unfavorable prognosis and mutations in key oncogenes. Its expression was linked to immunomodulatory factors, immune cell infiltration, and immunoreactivity scores in the tumor microenvironment. Additionally, ASCL1 influenced tumor immune dynamics and chemosensitivity in BC. Overexpression of ASCL1 enhanced BC cell proliferation, migration and invasion, while its knockdown had the opposite effect. Notably, inhibition of ASCL1 increased BC cell sensitivity to paclitaxel both in vitro and in vivo. In addition, inhibition of ASCL1 activated ferroptosis in BC, including altered mitochondrial morphology, increased MDA and ROS levels, decreased GSH levels and reduced GSH/GSSG ratio. Mechanistically, inhibition of ASCL1 decreases the phosphorylation of CREB1, thus reducing the expression of GPX4. In summary, inhibition of ASCL1 increases paclitaxel sensitivity by activating ferroptosis via the CREB1/GPX4 axis.ConclusionsASCL1 exerts oncogenic effects in BC and represents a potential therapeutic target for intervention.